Immediate and late impact of reperfusion therapies in acute pulmonary embolism. (21st November 2019) - Valerio, Luca; Klok, Frederikus A; Barco, Stefano
Abstract: Haemodynamic instability and right ventricular dysfunction are the key determinants of short-term prognosis in patients with acute pulmonary embolism (PE). Residual thrombi and persistent right ventricular dysfunction may contribute to post-PE functional impairment, and influence the risk of developing chronic thromboembolic pulmonary hypertension. Patients with haemodynamic instability at presentation (high-risk PE) require immediate primary reperfusion to relieve the obstruction in the pulmonary circulation and increase the chances of survival. Surgical removal of the thrombi or catheter-directed reperfusion strategies is alternatives in patients with contraindications to systemic thrombolysis. For haemodynamically stable patients with signs of right ventricular overload or dysfunction (intermediate-risk PE), systemic standard-dose thrombolysis is currently not recommended, because the risk of major bleeding associated with the treatment outweighs its benefits. In such cases, thrombolysis should be considered only as a rescue intervention if haemodynamic decompensation develops. Catheter-directed pharmaco-logical and pharmaco-mechanical techniques ensure swift recovery of echocardiographic and haemodynamic parameters and may be characterized by better safety profile than systemic thrombolysis. For survivors of acute PE, little is known on the effects of reperfusion therapies on the risk of chronic functional and haemodynamic impairment. In intermediate-risk PE patients, available data suggest that systemic thrombolysis may have little impact on long-term symptoms and functional limitation, echocardiographic parameters, and occurrence of chronic thromboembolic pulmonary hypertension. Ongoing and future interventional studies will clarify whether 'safer' reperfusion strategies may improve early clinical outcomes without increasing the risk of bleeding and contribute to reducing the burden of long-term complications after intermediate-risk PE.